2022
DOI: 10.1051/ro/2022018
|View full text |Cite
|
Sign up to set email alerts
|

Price decisions with asymmetric reference effect and information sharing in dual-channel supply chains

Abstract: This paper considers a retailer-manufacturer dual-channel supply chain (DCSC) consisting of a retail channel and a direct sale channel. Previous literature has shown that either asymmetric reference effect (ARE) or information sharing (IS) significantly impacts customers' demand, then the channel members' pricing decisions. As yet, no literature has examined the joint effect of both on the channel members' pricing decisions, especially in a DCSC. To fill up the deficiency, we first explore and compare the pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The results have shown that the impact of retail services on the pricing decisions of supply chain members is more pronounced. Zhao et al (2022) discussed the impact of asymmetric reference effect (ARE) on dual-channel supply chain decision making and found that ARE affects channel members differently when information is shared versus not shared. Wu et al (2023) investigated the effects of information sharing on optimal advertising expenditures, pricing mechanisms, manufacturer, and retailer performance, and found that manufacturers benefit from information sharing, while retailers benefit from the smaller market shares held by the retail channel.…”
Section: Pricing Decisions In Dual-channel Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have shown that the impact of retail services on the pricing decisions of supply chain members is more pronounced. Zhao et al (2022) discussed the impact of asymmetric reference effect (ARE) on dual-channel supply chain decision making and found that ARE affects channel members differently when information is shared versus not shared. Wu et al (2023) investigated the effects of information sharing on optimal advertising expenditures, pricing mechanisms, manufacturer, and retailer performance, and found that manufacturers benefit from information sharing, while retailers benefit from the smaller market shares held by the retail channel.…”
Section: Pricing Decisions In Dual-channel Supply Chainsmentioning
confidence: 99%
“…The results have shown that the impact of retail services on the pricing decisions of supply chain members is more pronounced. Zhao et al. (2022) discussed the impact of asymmetric reference effect (ARE) on dual-channel supply chain decision making and found that ARE affects channel members differently when information is shared versus not shared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our work is also related to the literature on a two-period dual-channel supply chain. Dual-channel supply chain with a single-period has been widely studied in the past few decades (e.g., [2,12,21,22,48]). In a recent, a multi-period dualchannel have been paid attention to some researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cattani et al [11] investigate the effects on profits and market share when the direct channel is introduced under specific pricing strategies. More recent research has investigated various topics, including channel coordination and contracts [8,9], pricing, service, and quality effort decisions [15], pricing decisions in the presence of multiple retailers [23], pricing and asymmetric reference effect [47], pricing and inventory decisions [21], pricing, quality, and stocking decisions [20], and the effect of information structure and risk aversion [33]. In the context of multi-channel distribution systems, Tahirov and Glock [41] carry out an exhaustive review of the manufacturer's drivers behind opening a direct channel and possible mechanisms to mitigate the channel conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%